Farmers' knowledge and perceptions of soil fertility - Crane, T. A; Traoré, B (Conflict, Social Capital and Managing Natural Resources, 2005)
This paper examines the subject of linking local knowledge with scientific research on soil fertility, in both theoretical and applied terms. The end goal of this effort is to collaborately develop improved soil management techniques via epistemological integration of local and scientific knowledge. A brief examination of some of the historical problems and failings of introduced agricultural technologies is presented. In an effort to explicate the shared and divergent perspectives, local knowledge systems and institutional scientific research are compared according to classificatory systems and fertility management regimes. The scientific bases for soil classification and soil fertility management are based on a review of the literature. The final part of this paper examines how cultivators in the Commune of Madiama in Mali have received and perceived scientific research.